ABCB1 Genotypes Predict Cyclosporine-Related Adverse Events and Kidney Allograft Outcome - Dario Cattaneo; Piero Ruggenenti; Sara Baldelli; Nicola Motterlini; Eliana Gotti; Silvio Sandrini; Maurizio Salvadori; Giuseppe Segoloni; Paolo Rigotti; Donato Donati; Norberto Perico; Giuseppe Remuzzi (2009)
Cyclosporine A (CsA) is a substrate of P-glycoprotein, an efflux transporter encoded by the ABCB1 gene. Compared with carriers of the wild-type gene, carriers of T allelic variants in exons 21 or 26 have reduced P-glycoprotein activity and, secondarily, increased intracellular concentration of CsA; therefore, carriers of T variants might be at increased risk for CsA-related adverse events. We evaluated the associations between ABCB1 genotypes (in exons 12, 21, and 26) and CsA-related outcomes in 147 renal transplant recipients who were receiving CsA-based immunosuppression and were included in the Mycophenolate Steroids Sparing study. During a median of 65.5 mo follow-up, carriers of T allelic variants in exons 21 or 26 had a three-fold risk for delayed graft function (DGF), a trend to slower recovery of renal function and lower GFR at study end, and significantly higher incidences of new-onset diabetes and cytomegalovirus reactivation compared with carriers of the wild-type genotype. T variants in both exons 21 and 26 were independently associated with 3.8- and 3.5-fold higher risk for DGF, respectively (P = 0.022 and P = 0.034). The incidence of acute rejection and the mean CsA dose and blood levels were comparable in genotype groups. In conclusion, renal transplant recipients with T allelic variants in ABCB1 exons 21 or 26 are at increased risk for CsA-related adverse events. Genetic evaluation may help to identify patients at risk and to modulate CsA therapy to optimize graft and patient outcomes.